Stability Analysis and Support Design of Imam Reza Tunnel in Ardabil Sarcham Road by Numerical Methods - Alireza Afradi; Siamak Rezazadeh (Salehan Institute of Higher Education, 2018)
Geological structures and performance of the geodynamic processes can affect engineering projects on their own. Hence, the stability analysis and designing methods for foreseeing the retaining and support system for tunnels are diverse and came from different points of view. So this study seeks to present stability analysis of Imam Reza tunnel in Ardabil Sarcham Road with a special focus on the impact of future earthquakes on its stability using numerical methods. In this study, first designing and operating the initial structure with the height of 5.5 m and a semi-circular cross section. Secondly, drilling with the height of 3m and the width of 7.34 m and with a rectangle cross section. For stabilization, Rock Mass Rating (RMR) geomechanical classification systems and methods used. At the stabilization level, the materials were examined in laboratory, regarding the properties of sides and roof of the tunnel and pressure on them. The results of physical and mechanical experiments shown that the compressive strength ranged from 400 kg/cm2 to 500 kg/cm2 on average. The elastic modulus is between 12 and 13 GPa for the rocks. The Cohesion (C) ranged from 4-5MPa to 5 MPa and the Angle of Internal Friction (φ) is between 60ᵒ and 50ᵒ.